The intergenerational effects of unemployment: How parental unemployment affects educational transitions in Germany - Kristina Lindemann; Markus Gangl (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This paper studies the intergenerational effects of parental unemployment on students' transitions after completing upper secondary education. Besides estimating the average treatment effect of parental unemployment on transition outcomes, we also aim to identify the economic, psychological or other intra-familial mechanisms that might be responsible for any adverse impact of parental unemployment on children's educational transitions. Using longitudinal data from the German Socio-Economic Panel and propensity score matching estimators, we indeed find that paternal unemployment has an adverse impact on the likelihood to enter tertiary education whereas maternal unemployment does not. We also find that the magnitude of the effect depends on the duration of unemployment. Even though we are unable to fully account for the underlying mechanisms, our mediation analysis suggests that the effect of paternal unemployment is not due to the loss of income, but relates to the negative consequences of unemployment for intra-familial well-being and students' declining optimism about their further academic opportunities.
Keywords: 330; intergenerational effects; educational inequalities; educational transitions; parental unemployment; propensity score matching